Comparative Genomic Analysis Of Mycobacterium Tuberculosis From Pulmonary And Central Nervous System Infections To Determine Factors Of Neurotropism - Saw, Seow Hoon (2019)
Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB) and the major mycobacterial species associated with central nervous system (CNS) infection. Tuberculous meningitis (TBM) is a global challenge due to difficulties with diagnosis, treatment and high mortality rate. It is not clear what factors promote CNS invasion and pathology in TB, but it has been reported that Mtb isolates from meningitis patients show specific genetic traits not found in respiratory isolates. Thus, in this study, genomic features of Mtb isolates from CSF and respiratory specimens were compared to identify factors that could contribute to neurotropism in the pathogenesis of CNS TB. First, suppression subtractive hybridisation (SSH) combined with T/A cloning technology was utilized to build a subtracted cDNA library of genes showing DNA sequence differences between two strains of Mtb from the CSF of Malaysian patients with meningitis and two strains from sputum samples. Subsequently, the whole genome sequences (WGS) of eight CSF strains from Malaysian patients presenting with TB meningitis (TBM) were analysed against the WGS of 30 to 85 respiratory strains, including the reference strain H37Rv, downloaded from public databases. All WGS were examined for gene rearrangements, indels, inversions, micro-variants, as well as structural and globularity changes in proteins. In addition, they were searched for homologs of genes previously reported to be associated with meningitis in Mtb and three other neuropathogens, Neisseria meningitidis, Streptococcus pneumoniae and Escherichia coli K1. With SSH, 7 subtracted DNA fragments of various sizes were generated. With the use of BLASTN and BLASTX, these subtracted sequences were shown to be similar to those found in Mtb strain isolated from the brain of an Indian patient. They encode mycobacterial PE/PPE proteins which play an important role in the evasion of host immune responses, and other conserved hypothetical proteins with unknown function. Genome-wide comparisons revealed rearrangements (translocations, inversions, insertions and deletions) and non-synonymous single nucleotide polymorphisms (ns SNPs) in the CSF-derived strains that were not observed in the respiratory Mtb genomes used for comparison. These rearranged segments were rich in genes for PE/PPE, transcriptional and membrane proteins. Similarly, most of the ns SNPs common in CSF strains were found in genes encoding PE/PPE proteins. Protein globularity differences were observed among mycobacteria from both CSF and respiratory sources and in proteins previously reported to be associated with TBM. Transcription factors and other transcription regulators featured prominently in these proteins. Homologs of TBM-associated genes were found in the WGS of Mtb, M. bovis, M. leprae, M. lepromatosis and two environmental non-tuberculous mycobacteria. However, only two of these homologs were identified in all eight CSF-derived Mtb genomes. Three homologs of 141 genes reported to be associated with S. pneumoniae meningitis and two of 164 virulence genes reported in N. meningitidis were also found in the CSF-derived Mtb genomes. The detection of common meningitis-associated genes in mycobacterial and non-mycobacterial neuropathogens raises speculations on the existence of a pan-bacterial mechanism of CNS infection. However, all the genes shared by CSF Mtb strains and other neuropathogenic bacterial spp. were also found to be common in the comparison respiratory Mtb genomes examined. Hence, although some genetic traits were found in CSF-derived but not sputumderived Mtb examined in this study, there are indications that neurotropic traits may not be specifically or universally found in Mtb causing CNS disease. Overall, the findings from this study suggest that CNS infection in TB is more likely to be directed by the expression of multiple virulence factors selected by the interaction between pathogen and host immune responses, than the presence of specific genetic traits.